PERANCANGAN BRANDING WISATA PEMANDIAN AIR PANAS PADUSAN PACET SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Latul, Dea Anindyta Putri; Fianto, Achmad Yanu Alif; Bahruddin, Muh (Jurnal ArtNouveau, 2014)
Padusan Pacet Hot Spring has great potential. However Padusan Pacet Hot Spring has not been promoted yet, so many people donât know about this. The purpose of Padusan Pacet Hot Spring design branding is to increase brand awareness. The methods used in this design is qualitative methods by doing interviews, observation, documentation, and literature studies. These things should be done in order to collect supporting data for the preparation of the branding design concept. The results from data collection and data analysis about Padusan Pacet Hot Spring are the keywords namelyÂ  âNatural and Calmâ. In this case, Padusan Pacet Hot Spring offers natural and calming concept of tourism that is very suitable for relaxation. Considering this tourist attractions is very potential and the absence of promotion activities to introduce this tourism to the general public, so the branding design for Padusan Pacet Hot Spring needs to be done in an effort to increase brand awareness.